Analysis of an Online Application-Based Accounting Information System in MSMEs (A Study of YoutFit Butik Kendari) - Dhea Rizki Herdiani Sahir; Andi Basru Wawo; Sulvariany Tamburaka (JURNAL ECONOMINA, 2026)
This study aims to determine how the application of an online application-based accounting information system in SMEs (Small and Medium Enterprises), this study uses qualitative methods using observation and interview methods. Based on the results of the research that has been done, the researcher found that there is an online application-based accounting information system in the SMEs YoutFit Butik Kendari. The company has used a digital application-based accounting information system that plays a role in recording financial transactions and preparing financial reports called the Olsera.com cloud. The application is a transaction and financial management service application. In the study, several obstacles were found that needed to be fixed, some of these obstacles could be overcome well. Overall, the Olsera.com system is sufficient to accommodate the needs of financial recording and accounting in the YoutFit Butik business